Similarities of Vietnam and South Korea – Linking to the Strategy Cooperation Partnership and Its Future Direction - Bach, Thi Ngoc Trang (International Journal of Social Sciences and Management, 2014)
The relationship of Vietnam and Korea was making by warmth, close friendship and understanding. On 22 December 1992, the two countries established the formal diplomatic relation, thus opening a new era in their bilateral ties. Since then, the friendship and cooperation between the two countries have been developing very dynamically in all areas. In 2001, during President of Vietnam Tran Duc Luong’s State visit to the Republic of Korea, both sides agreed to establish the “Comprehensive Cooperation Partnership in the 21st Century”. In October 2009, during President Lee Myung Bak’s State visit to Vietnam, relationship was upgraded to Strategic Cooperation Partnership, setting a new important landmark in Vietnam-Korea relations. The two countries are closely cooperating and developing in the fields of trade, investment, education and training, science and technology, culture and tourism, and through a wide spectrum of people-to-people contact. Vietnam and Korea shared many commonalities and similarities in the geographical and natural conditions as well as historical and cultural traditions. For example, Vietnam and South Korea have experienced thousands years in history and were much influenced by Confucianism. Both Vietnam and Korea from the ancient time were the poor agricultural countries with water rice production, which heavily depended on the natural conditions. Hence the peoples of the two countries have the same or very similar psychology, mentality and the way of life. With their basic characteristics, the two countries have plentiful literature treasures. The most important factor which has promoted the bilateral ties between the two countries is sharing the common interest of building a prosperous and happy country for its people in a peaceful, stable, friendly and cooperative environment in the region and the world over. The similarities between two countries shared interests in building a peaceful and stable world. DOI: http://dx.doi.org/10.3126/ijssm.v1i3.10573 Int. J. Soc. Sci. Manage. Vol.1(3) 2014: 88-92